Academic visit to the Arab Republic of Egypt - UiTM Shah Alam, Akademi Pengajian Bahasa (Academy of Language Studies, 2022)
The delegation of Academy Language Studies (APB), UITM led by Associate Professor Ts Dr Janudin Sardi went to the Arab Republic of Egypt as an academic visit from 5th to 12th September 2022. A meeting with Education Malaysia Egypt (EME) was held on the first day at Dewan Malaysia Abbasyah Cairo. The meeting was attended by EME ACADEMIC VISIT TO THE ARAB EPLIBUC OE EGYRT LIC OF EGYPT Utiveriti Teknologi MARA Malay الزيارة الأكاديمية إلى جمهورية مصر العربية. representative, Mr. Khairi Abdullah), Advisor for the Minister of Education, Malaysia (Mr. Hashim Zaini), First Secretary of Minister of Education, Malaysia together with Associate Professor Dr Janudin Sardi and a delegation from APB UITM.